NETWORK INTELLIGENCE AND THE EVOLUTION OF PUBLIC CONSCIOUSNESS IN THE DIGITAL AGE - Devterov, I. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2020)
The introduction talks about "strong" artificial intelligence, which is most often compared (and with good reason) with human. A number of cognitive tasks, decision-making in conditions of uncertainty, and other properties put it on the same level as HI (human intelligence), depriving it of subjectivity in some cases. What can, under certain assumptions, be included as an important, systemic aspect in the process of evolution of public consciousness. Purpose of research. The aim and tasks of this article is to explicate the concept of "network intelligence" (NI), which has not previously been considered in either philosophical or humanitarian studies. The importance of perception of cybersocium consciousness as a whole is based on the need to identify its system-forming factors, the main of which, according to the authors, is network intelligence, which forms the structure of social relations today. Research methods of studying the evolution of social consciousness are associated with the dichotomy of natural and artificial intelligence. The dialectical and systematic nature of their interaction is obvious. As a research result of using these methods, it was found that the dual structure "society-Internet" based on AI ("artificial intelligence") is a new entity, which the author called "network intelligence" (NI). In the course of discussing these issues, the author draw the reader's attention to such phenomena as the freedom of network users, their identity, and the ability to integrate with AI. An important role is given to understanding the changes that have occurred in society. Conclusion. Society's entry into the digital world has both positive and negative aspects. The creation of a single global digital field is one of the most important factors in the progress of society and, as a result, the evolution of public consciousness in the XXI century. Network intelligence is the fundamental platform on which all this will happen.